Electrophoretic separation of chiral agrochemicals using neutral cyclodextrin based dual selector system - Wan Ibrahim, Wan Aini (Faculty of Science, Universiti Teknologi Malaysia, 2009)
The enantiomeric separation of chiral agrochemicals was investigated using dual systems with mixtures of cyclodextrin derivatives. The dual cyclodextrin systems consist of two neutral cyclodextrin, namely hydroxypropyl- Î³-cyclodextrin (HP-Î³-CD) and hydroxypropyl-Î²-cyclodextrin (HP-Î²-CD). The agrochemicals used were three triazole fungicides viz. cyproconazole, bromuconazole and diniconazole, each with 2, 2 and 1 stereogenic centre respectively. Results showed that dual CD systems are useful to achieve and to optimize chiral separations of compounds not sufficiently separated with single CD alone. The best dual chiral recognition mode for the complete and simultaneous separation of propiconazole, bromuconazole, and diniconazole enantiomers was achieved with a mixture of 27 mM HP-Î²-CD and 3 mM HP-Î³-CD at pH 3.0 in the phosphate buffer containing 40 mM sodium dodecyl sulfate (SDS) and 10%:5% v/v methanol : acetonitrile as organic modifiers.